Status of Anaemia among the Tribal Women in Manipur - H. Sorojini Devi (Archives of Current Research International, 2018)
Background: Anaemia is the most common nutritional deficiency disorder in the world. It is becoming a very common problem affecting both genders of all the ages and affects children, adolescents and women of reproductive age worldwide. Objective: To examine the status of anaemia among the tribal women of reproductive age (15-49 years). Setting: The study was conducted in seven villages of Chandel, Kangpokpi and Churachandpur district in Manipur. Design: A Cross-sectional study. Subject and Methods: A cross-sectional data of 282 women of reproductive age (15-49 years) were randomly chosen from Chothe, Vaiphei and Kom tribal women of Manipur. Haemoglobin estimation in gram per decilitre of each subject was estimated by acid Hematin (Sahli’s method) using haemoglobinometer. Results: Anaemia prevalence of 38.95% (Vaiphei) 32.29% (Kom) and 17.58% (Chothe) in the mild and moderate grades were observed among the women. Mean values of haemoglobin of different age groups indicated that the age group 15-25 years in each case shows the lowest haemoglobin values with 12.82% g/dl, 11.87% g/dl and 11.83% g/dl as compared to higher age groups. Range values of the present study indicated that the higher haemoglobin ranges were found among the Chothes than the Vaiphei and Kom women. The highest literacy rate was also found among the Chothe women (58.24%) and the lowest percentage was represented by the Vaiphei women (48.24%). Small sections of the women had an idea about anaemia, but the majority of them remained as ignorant about this problem.